Changement social et délinquance des adolescents, une analyse à la lumière des écrits de Denis Szabo - LeBlanc, Marc (Criminologie, 1993)
This article is about social change and it has Denis Szabo 's writings as a starting point. We compare the 1960 and 1970 affluent society delinquency with the 1980 and 1990 scarcity society delinquency. We conclude that withstanding structural and modal personality changes, the nature and the level of self-reported delinquency of adolescent did not change. We introduce the notions of homeostasis and homeoresis to explain these results.